2009
DOI: 10.1103/physrevc.79.044905
|View full text |Cite
|
Sign up to set email alerts
|

Ratios of heavy baryons to heavy mesons in relativistic nucleus-nucleus collisions

Abstract: Heavy baryon/meson ratios c /D 0 and b /B 0 in relativistic heavy ion collisions are studied in the quark coalescence model. For heavy baryons, we include production from coalescence of heavy quarks with free light quarks as well as with bounded light diquarks that might exist in the strongly coupled quark-gluon plasma produced in these collisions. Including the contribution from decays of heavy hadron resonances and also that due to fragmentation of heavy quarks that are left in the system after coalescence, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 77 publications
8
132
0
Order By: Relevance
“…We have found that the Λ c /D 0 1.5 at the peaks at p T 2.5 GeV at RHIC energies and Λ c /D 0 0.8 in the p T 0 region. Similar results have been predicted in [2]. We observe that at LHC energies due to the fact that fragmentation start to be the dominant hadronization mechanism for the D meson production this ratio is predicted to be smaller at higher energies.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We have found that the Λ c /D 0 1.5 at the peaks at p T 2.5 GeV at RHIC energies and Λ c /D 0 0.8 in the p T 0 region. Similar results have been predicted in [2]. We observe that at LHC energies due to the fact that fragmentation start to be the dominant hadronization mechanism for the D meson production this ratio is predicted to be smaller at higher energies.…”
Section: Discussionsupporting
confidence: 77%
“…The inclusion of fragmentation reduce the ratio and we can see that in the peak region we get a quite good agreement with the only experimental data. Notice that in our calculation we obtain similar baryon/meson ratio to the one predicted in [2]. Compared with measured light baryon/meson ratios likep/π − and Λ/K 0 S ratios (see [18][19][20] heavy quarks.…”
Section: Charmed Hadrons Transverse Momentum Spectra and Ratiosupporting
confidence: 63%
See 1 more Smart Citation
“…For the heavy meson [103], we obtain ΛD = 1.35Λ N and Λ B = 1.29Λ N for theD ( * ) meson and the B meson, respectively. For the heavy baryon [106], we obtain Λ Λc ∼ Λ Σc ∼ Λ N for the charmed baryon, and Λ Λ b ∼ Λ Σ b ∼ Λ N for the bottom baryon. We note that values of these cutoffs are smaller than those used in other studies, e.g.…”
Section: Model Setupmentioning
confidence: 99%
“…The nucleon cutoff is determined to reproduce the deuteronbinding energy by the OPEP as Λ N = 837 MeV [103][104][105]. The ratios are computed by the means of constituent quark model with the harmonic oscillator potential [106], where the frequency is evaluated by the hadron charge radii in Refs. [107,108].…”
Section: Model Setupmentioning
confidence: 99%